Compound In Vivo Inactivation of Pml and p53 Uncovers a Functional Interaction in Angiosarcoma Suppression - Papa, Antonella (SAGE Publications, 2012)
The promyelocytic leukemia (PML) tumor suppressor gene was initially identified as part of the t(15:17) chromosomal translocation associated with acute promyelocytic leukemia (APL). The PML protein is responsible for the assembly and function of characteristic nuclear domains known as PML-nuclear bodies (PML-NBs), which have been implicated in a variety of cellular functions, including growth suppression, apoptosis, and cellular senescence. PML’s many roles have been linked, at least in part, to its functional interaction with the tumor suppressor p53. It has been shown that PML favors both p53 accumulation and transcriptional activity; in turn, PML expression is directly regulated by p53, and this reciprocal regulation contributes to p53-mediated apoptosis and senescence. Nevertheless, genetic proof and in vivo assessment of the relevance of this functional crosstalk are still missing. Here we show that complete Pml inactivation, in a context of p53 heterozygosity, redistributes and expands the tumor spectrum leading to the formation of angiosarcomas and increased lymphomagenesis. Importantly, we find that Pml inactivation decreases the rate of loss of heterozygosity (LOH) in the remaining p53 allele, revealing the relevancy of p53 haploinsufficiency to tumorigenesis. Our results thus lend in vivo genetic support to the importance of the crosstalk between these two critical tumor suppressor genes.